The question of reality - Munitz, Milton K. (Milton Karl), 1913-1995 (Book collections on Project MUSE., 1990)
"When we read that scientists have come close to pinpointing the "origin of the universe" by means of a Big Bang cosmology, or are engaged in formulating a "theory of everything," as in current ten-dimensional superstring theories of particle physics, can we doubt that such inquiries or their results inevitably raise important philosophical questions? In the present book, as well as in his previous work Cosmic Understanding, the renowned philosopher Milton Munitz attempts to answer some of these questions by examining recent scientific theories of cosmology in a philosophical context"--Publisher description